Effect of monensin on grain bloat in cattle - M.L. Coe; N. Wallace; Kenneth E. Kemp; J.C. Parrott; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1996)
Twelve ruminally cannulated Holstein steers were used to determine the effect of monensin (0, 20, 30, and 40 g/ton) on grain bloat. Steers were fed a bloat-provocative, high-grain diet at 1% of body weight twice daily. Monensin premix was added directly to individual steers diets at the time of feeding. The severity of bloat was scored daily on a scale of 0 (no bloat) to 5 (severe bloat). The scoring was based on the degree of frothiness and abdominal distention. Bloat scores (mean of wk 2, 3, and 4) were lower (P<.0l) for monensin-fed steers than for the controls. The mean bloat scores were 1.43, 1.18, 1.00, and .93 for 0, 20, 30 and 40 g/ton monensin, respectively. Total gas production during in vitro ruminal fermentation tended to be higher (P=.12) for control than for monensin-fed steers. Ruminal pH and total volatile fatty acid concentrations were unaffected by treatment. Monensin decreased frothy bloat caused by the bloat-provocative diet, and the degree of control appeared to be greater with higher levels of monensin.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Monensin; High grain diet; Frothy bloat